Wide-awake foot and ankle surgery: A retrospective analysis. Issue 4 (December 2017) - MacNeill, A. Luke; Mayich, D. Joshua
Highlights: We assess the patient experience associated with "wide-awake" foot and ankle surgery. Former patients were surveyed about their perioperative anxiety, pain, and satisfaction. Patient anxiety was low and decreased steadily over the perioperative period. Patients generally experienced little or no intraoperative pain. Patients reported high satisfaction with their surgical experience. Abstract: Background: The "wide-awake" approach to foot and ankle surgery is characterized by a surgeon-administered mixture of local anesthetic and epinephrine. No tourniquet, sedation, or general anesthesia are required for surgery. This paper describes a retrospective survey of the initial patients to undergo wide-awake foot and ankle surgery at our center. Methods: Thirty former wide-awake patients were surveyed about their perioperative anxiety, pain, and satisfaction. Results: Twenty-seven of 30 patients (90%) completed the survey. Patients received a variety of forefoot, hindfoot, and lower leg procedures. In general, they reported a decrease in anxiety over the course of the perioperative period ( p  = 0.005). Pain fell from the preoperative to the intraoperative period, then rose to preoperative levels during recovery ( p  < 0.001). Most patients said that the surgery was better than expected (83%); would choose wide-awake surgery for a subsequent procedure (87%); and would recommend wide-awake surgery to someone who required surgery (88%). Conclusions: Results indicate that the wide-awake approach to foot and ankle surgery causes little discomfort to patients who receive many common procedures. The removal of hindfoot hardware under local anesthesia is contraindicated.